Importance of parathyroid hormone assessment in a known case of ulcerative colitis and recurrent pancreatitis - A. V. V. A., Veena Santoshi; Sreeram Praveen, Matti; Reddy, D. Nageshwar (International Surgery Journal, 2025)
Gastrointestinal diseases like acute pancreatitis, ulcerative colitis, peptic ulcer may be associated with hyperparathyroidism which may be primary or secondary. These conditions associated with parathyroid adenoma is rare in the literature globally. Here we present a 43 years old female patient who was treated for ulcerative colitis and probably drug induced pancreatitis as initial impression in other health care facility but without any relief. When consulted at our health facility, she was systematically and rationally investigated for hyperparathyroidism and was diagnosed to have parathyroid adenoma. She was operated and now reported to have relieved of her symptoms. This case report thus demonstrates importance of investigating patients of ulcerative colitis with pancreatitis for hyperparathyroidism.